2022
DOI: 10.1007/s00198-022-06561-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist interventions in osteoporosis management: a systematic review

Abstract: Internationally, there is an osteoporosis treatment gap, which pharmacists may assist in closing. This review identifies pharmacist interventions for improving osteoporosis management and evaluates their effectiveness. Pharmacist interventions are shown to improve osteoporosis management in terms of increasing investigation and treatment commencement and osteoporosis therapy adherence. Introduction This review identifies pharmacist interventions for improving osteoporosis management and evaluates their effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(316 reference statements)
0
5
0
Order By: Relevance
“…Consequently, aged care resident-specific fracture risk assessment tools to guide management have been developed [ 16 , 37 ]. Completing fracture risk assessment tools and participating in case conferences that enable clinical discussion are examples of a non-dispensing service embedded pharmacists could undertake as part of an interdisciplinary team to improve osteoporosis management [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, aged care resident-specific fracture risk assessment tools to guide management have been developed [ 16 , 37 ]. Completing fracture risk assessment tools and participating in case conferences that enable clinical discussion are examples of a non-dispensing service embedded pharmacists could undertake as part of an interdisciplinary team to improve osteoporosis management [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic literature review found that pharmacists undertaking non-dispensing services can improve osteoporosis management [ 29 ]. Utilising these services, pharmacists increased osteoporosis investigation, treatment commencement and adherence [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is likely due to lack of awareness and robust evidence to support the role of collaborative medication reviews for patients with minimal trauma fracture. Indeed, recent systematic reviews reporting pharmacist interventions for patients with osteoporosis highlighted a range of interventions but no studies included pharmacist-led medication reviews 56 57. This trial is intended to determine whether incorporating collaborative medication reviews in the transition between tertiary care and primary care can optimise medication management for patients with minimal trauma fracture.…”
Section: Discussionmentioning
confidence: 99%